Passive and social screen time in children with autism and in association with obesity - Aviva Must; Misha Eliasziw; Heidi Stanish; Carol Curtin; Linda G. Bandini; April Bowling; April Bowling (Frontiers Media S.A., 2023)
BackgroundScreen time has been identified as a risk factor for childhood obesity, but the media landscape has evolved rapidly. Children with autism tend to be heavy users of screens and have an elevated prevalence of obesity. We know little about screen use patterns among children with autism vs. typically developing (TD) peers and in association with obesity.MethodsBaseline data from 10,842 participants in the Adolescent Brain Cognition Development Study was used to characterize time spent with child-reported passive screen use (television/movies/watching videos), playing video games, and using social media. Duration of screen time by autism status and gender was summarized as mean time per day; obesity was defined using CDC/WHO criteria. A propensity score analysis was used to create a matched dataset for analysis.ResultsOverall, 1.7% of children were was identified as having autism. Significant mean differences were observed by autism status and gender for both passive viewing and playing video games. Compared to TD children, boys with autism spent more time (2.9 vs. 2.3 h, p < 0.001) watching TV, movies or videos, as did girls (3.0 vs. 2.0 h, p = 0.002). Compared to TD peers, boys with autism reported more video game time (102.7 vs. 77.5 min, p = 0.001), as did girls with autism (64.4 vs. 37.9 min, p = 0.03); girls with autism also spent more time on social media sites or video chat (45.5 vs. 21.9 min, p = 0.04). Overall, obesity prevalence increased with increasing screen time duration, significantly for passive screen time (p-value = 0.002) and texting (p-value = 0.02). Associations between obesity and screen time duration did not differ by autism status.DiscussionChildren with autism spend more time playing video games and on passive and social screen activities than their TD peers, with some variations by gender. High rates of social media use among girls with autism and multiplayer video game use among both boys and girls with autism may challenge the notion that the high levels of screen time reflect social isolation in the group. Given potential positive aspects of screen time in children with autism movement to focus on content and context is appropriate.